Simulation of Nakagami fading channels with arbitrary cross-correlation and fading parameters. - Keli Zhang
Nakagami fading model is widely used in modeling wireless communication systems. In this paper, we present methods to generate Nakagami fading signals with arbitrary cross-correlation and fading parameters by taking the square root of correlated Gamma random variables (RVs) with the corresponding shape parameters. To generate correlated Gamma RVs with different noninteger values of m-parameters, two methods, namely the decomposition method and Sim's method, are proposed. The former is more flexible and efficient. The latter is mathematically exact but carries constraints on the permissible simulation parameters. Simulations show that both methods produce outputs that match well with the specifications.
Keywords: Nakagami fading channels; Arbitrary cross-correlation parameter; Correlated gamma random variables; Decomposition method; Fading parameter; Mobile radio communication channel; Wireless communication system